2017
DOI: 10.1016/j.fertnstert.2017.07.488
|View full text |Cite
|
Sign up to set email alerts
|

Cohort embryo selection (CES): a quick and simple method for selecting cleavage stage embryos that will become high quality blastocysts (HQB)

Abstract: significantly increasing the laboratory workload. Further investigation of ploidy status from Day 7 embryos may explain the lower implantation rate.References: 1. Su, Yu, et al. Aneuploidy analysis in day 7 human blastocysts produced by in vitro fertilization. Reproductive Biology and Endocrinology 14.1 (2016): 20. 2. Li, M., et al. Day 7 blastocysts, should they be discarded or cryopreserved?. Fertility and Sterility 90 (2008): S427.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In 2017, we reported that the simultaneous evaluation of patients' entire embryo cohort at a single time-point could improve the identification of embryos with the highest potential to form a blastocyst [37]. We observed a higher overall blastocyst formation prediction rate with the cohort selection method (CM), compared to standard morphology grading by expert embryologists and time-lapse scoring (95% vs. 86% and 89%; p = 0.06 and p = 0.21, respectively).…”
Section: Evaluating Resultsmentioning
confidence: 99%
“…In 2017, we reported that the simultaneous evaluation of patients' entire embryo cohort at a single time-point could improve the identification of embryos with the highest potential to form a blastocyst [37]. We observed a higher overall blastocyst formation prediction rate with the cohort selection method (CM), compared to standard morphology grading by expert embryologists and time-lapse scoring (95% vs. 86% and 89%; p = 0.06 and p = 0.21, respectively).…”
Section: Evaluating Resultsmentioning
confidence: 99%
“…This study demonstrated the ability of embryologists to quickly identify high-quality cleavage-stage embryos when all embryos in the cohort were simultaneously compared in a single image. This method of selection outperformed traditional methods of cleavage-stage embryo ranking based on both morphology and adjunctive morphokinetic TLI parameters (Dimitriadis et al, 2017). This method is excellent at identifying high-quality embryos from a cohort; however, this method of selection is subjective and lacks consistency between operators.…”
Section: Ai Application On Cleavage Stage Embryosmentioning
confidence: 97%
“…Embryoselectionisthemostimportantphaseafterthegradingisdone.Theselection ofembryomainlydependsonwhichdaytheembryoisbeingconsideredsothatithas thehighestchancesoffertility.CohortEmbryoSelectionmethodisbeingusedforthe assessmentanditusesthetimepointsandthedayofembryosthathavethehighest chance of implantation (Dimitriadis, 2017). In analyzing the high-quality embryo, thisisasimpleandnovelmethod.…”
Section: Ai In Embryo Classificationmentioning
confidence: 99%